From language lab to breakout rooms. Innovative methods in teaching Finnish phonetics online - Santoo, Laura (Activation-innovation-inspiration in (glotto) didactics, 2022)
Due to the pandemic, all the courses at the Institute of Scandinavian and Finnish Studies at the University of Gdańsk were organised online during the academic year 2020—2021. Due to this, teachers did not have access to the Language Lab, which is specially designed for speaking activities and teaching phonetics. Therefore, the course had to be planned again by modifying the exercises to be taught online. Phonetics combines theory with practical exercises such as dictations, games, and pair work. The aim of the exercises, often carried out through a game play, is to teach the students how the Finnish sound system differs from the Polish one (Polish being the native language of the students) and familiarise them with these sounds. Several aspects were chosen for the article to show how a course of phonetics and Language Lab activities can be organised online. The article also covers the importance of teaching and learning phonetics and why games are a crucial part of teaching for various reasons, such as offering the students a stress-free environment to practice what they are being taught and interact with each other.